Conspecific olfactory preferences and interspecific divergence in odor cues in a chickadee hybrid zone. Issue 17 (1st August 2019) - Van Huynh, Alex; Rice, Amber M.
Abstract: Understanding how mating cues promote reproductive isolation upon secondary contact is important in describing the speciation process in animals. Divergent chemical cues have been shown to act in reproductive isolation across many animal taxa. However, such cues have been overlooked in avian speciation, particularly in passerines, in favor of more traditional signals such as song and plumage. Here, we aim to test the potential for odor to act as a mate choice cue, and therefore contribute to premating reproductive isolation between the black‐capped ( Poecile atricapillus ) and Carolina chickadee ( P. carolinensis ) in eastern Pennsylvania hybrid zone populations. Using gas chromatography–mass spectrometry, we document significant species differences in uropygial gland oil chemistry, especially in the ratio of ester to nonester compounds. We also show significant preferences for conspecific over heterospecific odor cues in wild chickadees using a Y‐maze design. Our results suggest that odor may be an overlooked but important mating cue in these chickadees, potentially promoting premating reproductive isolation. We further discuss several promising avenues for future research in songbird olfactory communication and speciation. Abstract : Chemical cues have been shown to act in premating reproductive isolation across many animal taxa. However, this has not been demonstrated in any avian species. Here, we show how olfaction may be acting in reproductive isolation within the black‐capped and Carolina chickadee natural hybrid zone.